Mad Users’ World - Paradox of Users and Polluters!! - Make A Breakthrough in Environmental Accounting - Muninarayanappa, M. (European Scientific Journal, ESJ, 2017)
If sustainability becomes part of expectations held by society, it must become a business goal-this ensures ongoing survival/competitiveness. Providing information about social and environmental performance will increase the trust a community has in the organization. Entity is treated as distinct from owners and ignores externalities caused by the reporting entity, expenses not controlled by the entity are excluded and externalities caused by the entity can not be reliably measured and so not recognized. This is the contention. This article is conceptual in nature and used secondary data. The limitations of the study are that primary data with secondary data can give a better interpretation. The current attempt is to leave the planet in the same state at the end of the accounting period as it was in the beginning by one the modes of accounting to create responsibility to the users and produces.